Traumatic brain injury in children and adolescents in Brazil: An epidemiological approach (Research, Society and Development, 2023)
Introduction: Cranioencephalic Trauma is any trauma that attacks the skull and/or brain. In Brazil, this trauma is an important cause of morbidity, generating high hospital costs and length of stay. Intracranial trauma in children and adolescents is little debated. The objective is to discuss the epidemiology of traumatic brain injury in the child and adolescent population between the years 2012 and 2022 in Brazil. Methods: Descriptive-analytical study, with the DATASUS database on intracranial trauma in individuals aged 0 to 19 years in Brazil between the years 2012 to 2022. Results: There were 247,116 hospitalizations resulting in 8,936 deaths with a mortality rate of 3.61 %, with a relative cost of R$266.30 reais/day with a length of stay of 4.2 days. The epidemiological profile of patients with intracranial trauma is of brown men between 15 and 19 years old, mostly from the southeastern region. Discussion: Child and adolescent morbidity and mortality is higher among individuals aged 15 to 19 years, with an extensive intra-hospital cost due to clinical-surgical interventions due to infections or drainage of intracerebral hematomas. The out-of-hospital cost is little discussed and is related to care for sequelae, prevention of new injuries and specialized multidisciplinary follow-up. Conclusions: Intracranial trauma in children and adolescents is an important problem in our environment, with social and functional losses, and related deaths, and it is necessary to act with preventive actions against the events that cause the trauma.